Exogenous Antioxidants—Double-Edged Swords in Cellular Redox State: Health Beneficial Effects at Physiologic Doses versus Deleterious Effects at High Doses. Issue 4 (2010) - Bouayed, Jaouad; Bohn, Torsten
Abstract : The balance between oxidation and antioxidation is believed to be critical in maintaining healthy biological systems. Under physiological conditions, the human antioxidative defense system including e.g., superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione (GSH) and others, allows the elimination of excess reactive oxygen species (ROS) including, among others superoxide anions (O2 .- ), hydroxyl radicals (OH . ), alkoxyl radicals (RO . ) and peroxyradicals (ROO . ). However, our endogenous antioxidant defense systems are incomplete without exogenous originating reducing compounds such as vitamin C, vitamin E, carotenoids and polyphenols, playing an essential role in many antioxidant mechanisms in living organisms. Therefore, there is continuous demand for exogenous antioxidants in order to prevent oxidative stress, representing a disequilibrium redox state in favor of oxidation. However, high doses of isolated compounds may be toxic, owing to prooxidative effects at high concentrations or their potential to react with beneficial concentrations of ROS normally present at physiological conditions that are required for optimal cellular functioning. This review aims to examine the double-edged effects of dietary originating antioxidants with a focus on the most abundant compounds, especially polyphenols, vitamin C, vitamin E and carotenoids. Different approaches to enrich our body with exogenous antioxidants such as via synthetic antioxidants, diets rich in fruits and vegetables and taking supplements will be reviewed and experimental and epidemiological evidences discussed, highlighting that antioxidants at physiological doses are generally safe, exhibiting interesting health beneficial effects.